Sexual Abuse In Adolescents. Is it still happening? - Wulan Aprida Choirunnisa; Herman Nirwana; Syahniar Syahniar (Jurnal Aplikasi IPTEK Indonesia, 2020)
Sexual harassment is increasingly prevalent. This is a concern because most sex offenders are teenagers. Sexual harassment committed by adolescents is related to the psychological development they are undergoing. Adolescence is a transitional period between children and adults characterized by ongoing processes of change in biological, psychological and sociological terms. Adolescent students live their lives in school throughout the day, if calculated spending about 7 hours/day at school This study aims to describe the sexual abuse behavior of adolescents. The research sample consisted of 182 vocational students who were selected by the proportional random sampling technique. The instrument used was a scale of sexual harassment behavior. The research instrument was tested for validity and reliability The data analysis in this study used a quantitative approach with descriptive methods. The results showed that the acts of adolescent sexual harassment, in general, were in the high category of 76 students (42%). The implications of this study are as a basis for counselors to prevent acts of teenage sexual harassment in schools.